350 New Service of Intravenous Antibiotics Administration at Home- a Single Centre Experience. (28th February 2022) - Bista, A.; Singh, H.; Unnithan, A.; Das, G.; Kesawarini, D.; Bristoll, S.; Lewis, N.; Alnoori, N.
Abstract: Introduction: Outpatient Parenteral Antibiotics Therapy (OPAT) provides a safe and effective alternative to prevent a long-term hospital stay. If used efficiently, it is beneficial and cost-effective. Method: 199 patients from January 2017 since the services started to March 2021 were included in this retrospective observational study. Demographics, clinical management and OPAT outcome data were studied and compared with local guidelines. Patients receiving services for oral medications or ambulant to reach AECU were excluded. Results: 205 patients received the service with a total of 248 patient episodes. 6 patients were excluded because of inadequate data availability. 199 cases were analysed with a mean age of 72±13.9 years (age ≥60 years: 79.8%; M:F 3:2). 24.6% cases were osteomyelitis followed by 12% prosthetic infections. The average duration of antibiotics received was 38.4 days (3–187 days). We assumed 3 days as a benchmark for duration deviated from the planned duration and found 45% of patients got more antibiotics than they were planned: with an average of 20 days excess. 65.8% of patients had microbiological investigations done before antibiotics. Flucloxacillin was the first-choice antibiotic. When compared to the trust guidelines, 29% of patients were managed in line with the recommended duration, proper investigations, and choice of antibiotics. 14.5% of patients developed side effects. Conclusions: With this being a new service, there are a lot of opportunities to improve monitoring, patient experience and safe clinical practice. We have already started the improvement by changing our record-keeping for clinical governance and are working on the clinical pathway.